FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN UMKM (STUDI KASUS PADA UMKM DI KOTA BOGOR) - Eka Merdekawati; Novi Rosyanti (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
SMEs in the city of Bogor need to be developed because the existence of MSMEs can help increase economic growth and increase regional income.  The purpose of this study is to analyze that accounting understanding and marketing strategies are factors that influence the success of MSMEs in Bogor City. The sampling technique used in this study is convenience sampling method. The sample used in this study were 41 SME owners located in Central Bogor City. The analysis technique used is the analysis of the Mutivariat dependencies using multiple regression. The results showed that Accounting Understanding influences the Success of MSMEs in Bogor City with the conclusion that H1 was accepted. While the marketing strategy has no effect on the success of SMEs in the city of Bogor with the conclusion H2 is rejected. This implies that in the future the UMKM party will increase the understanding of accounting to support the UMMM success.